Preparation method of two-phase Mo-Mo5SiB2 alloy
The structure and mutual contact rate of Mo powder are adjusted by the preparation method to achieve continuous distribution of Mo phases, solving the problem that the two-phase Mo-Si-B alloy is difficult to match at room temperature and high temperature performance, and significantly improving the fracture toughness and high-temperature oxidation resistance of the alloy.
Patent Information
- Application Number
- CN202310276185.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The existing two-phase Mo-Si-B alloys are difficult to effectively match the performance of room temperature and high temperature, which limits their application in the industrial field.
The preparation method includes ultrasonic screening of Mo powder with anhydrous ethanol to obtain a uniform size Mo powder, and preparing a sheet-like molybdenum powder by a drum ball mill. Then the sheet-shaped molybdenum powder and T2 phase powder were subjected to low-energy mixing, followed by hot pressing and sintering, and the ball ratio, rotation speed and ball milling time were adjusted to control the structure of the molybdenum powder and achieve continuous distribution of the Mo phase.
The high room temperature fracture toughness and excellent high temperature oxidation resistance of two-phase Mo-Mo5SiB2 alloy are achieved, which significantly improves the overall performance of the alloy.
Smart Images

Figure CN116240413B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy preparation technology and relates to a preparation method of a two-phase Mo-Mo5SiB2 alloy. Background Art
[0002] With the rapid development of aviation, aerospace, new energy and other fields, the requirements for high-temperature structural materials are becoming more and more stringent, requiring not only good processing formability, but also excellent high-temperature oxidation resistance and creep resistance. Mo-Si-B alloy, especially Mo-Si-B alloy containing both tough phase α-Mo and intermetallic compound Mo5SiB2 phase with excellent high-temperature oxidation resistance, is one of the candidate materials for the new generation of high-temperature structural materials due to its excellent comprehensive performance.
[0003] In the Mo-Si-B alloy composed of α-Mo phase, intermetallic compound Mo3Si phase and Mo5SiB2 phase, α-Mo phase is the only tough phase and has excellent room temperature fracture toughness. Other studies have shown that continuously distributed and coarse-grained Mo can increase the probability of crack capture and crack bridging during deformation and fracture of the alloy, thereby further improving its fracture toughness. However, it reacts with O2 above 600°C to form MoO3, which is extremely volatile and causes severe weight loss of the alloy at high temperatures, making the alloy's oxidation resistance poor. The intermetallic compound T2 phase (Mo5SiB2) has excellent high-temperature oxidation resistance but is affected by its intrinsic brittleness, resulting in poor room temperature toughness of the alloy. Therefore, the researchers considered giving full play to the outstanding advantages of the α-Mo phase and the Mo5SiB2 phase to prepare a two-phase Mo-Mo5SiB2 alloy, so that the alloy has excellent high-temperature oxidation resistance while maintaining a high room temperature fracture toughness. However, too much α-Mo phase will make the alloy's high-temperature oxidation resistance poor, and too much intermetallic compound phase will reduce the alloy's room-temperature fracture toughness. As a result, the two-phase Mo-Si-B alloy always has the problem of difficult to effectively match room-temperature and high-temperature performance, limiting its application in the industrial field. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a two-phase Mo-Mo5SiB2 alloy, which solves the problem in the prior art that the room temperature and high temperature properties of the two-phase Mo-Si-B alloy are difficult to effectively match.
[0005] The technical solution adopted by the present invention is a method for preparing a two-phase Mo-Mo5SiB2 alloy, comprising the following steps:
[0006] Step 1, putting Mo powder and anhydrous ethanol into a polyethylene tank, encapsulating and drum-milling, and then drying to obtain flaky molybdenum powder;
[0007] Step 2, performing low-energy mixing treatment on the flaky molybdenum powder and the T2 (Mo5SiB2) phase powder to obtain a Mo-Si-B two-phase mixed powder;
[0008] Step 3: placing the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering, and obtaining a two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution after cooling.
[0009] The present invention is also characterized in that:
[0010] Before step 1, the Mo powder is screened to obtain Mo powder with uniform size.
[0011] The screening process is as follows: Mo powder and anhydrous ethanol are poured into a beaker, the mass ratio of anhydrous ethanol to powder is 1 to 5:1, the upper layer of liquid is poured out after ultrasound, and the large-sized powder on the lower layer is retained; then it is placed in a vacuum drying oven for drying, the drying temperature is 80°C to 150°C, the time is 12h to 24h, and finally sieved with 300 mesh to obtain Mo powder of uniform size.
[0012] In step 1, the mass ratio of Mo powder to anhydrous ethanol is 1:1 to 5:1.
[0013] The ball milling jar used in the ball milling process in step 1 is made of polyethylene, the grinding balls are made of alumina, and the ball milling parameters are: rotation speed 300-500 rpm, ball-to-material ratio 3:1-10:1, and ball milling time 10h-20h.
[0014] In step 2, the volume fraction of the flaky molybdenum powder is 30%-50%, and the volume fraction of the T2 phase powder is 50%-70%.
[0015] The mixing process in step 2 is ball milling. The ball milling jar and grinding balls used in the ball milling process are both made of agate. The ball milling parameters are: rotation speed 300 rpm, effective time 6 hours, and ball-to-material ratio of 1:1.
[0016] The parameters of the hot pressing sintering process in step 3 are: temperature of 1500℃~1600℃, heating rate of 10℃ / min, 7×10 -3 Pa~1×10 -2 Pa vacuum environment, the hot pressing pressure is 40-45MPa, and the time is 2h-6h.
[0017] The beneficial effects of the present invention are as follows: the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention controls the size of the flaky structure of the molybdenum powder under the conditions of adjusting the ball-to-material ratio, the rotation speed and the ball milling time, so as to obtain flaky Mo powder with a smooth, complete and crack-free surface; the flaky Mo powder is mixed with the T2 phase powder in a certain proportion, because the flaky Mo powder has a higher specific surface area, in the mixed powder of the flaky Mo powder and the spherical T2 powder, the probability and degree of mutual contact are higher, and in the subsequent hot pressing sintering process, it is easy to achieve the continuous distribution of the Mo phase, which can improve the ability of crack capture and crack bridging during the deformation and fracture of the alloy, and obtain the continuous distribution structure of the molybdenum phase with less Mo content, thereby improving the fracture toughness of the alloy; by changing the content, size and distribution of each phase, the organizational structure of the alloy is regulated, especially the minimum Mo content range of the two-phase alloy with a continuous Mo distribution structure is obtained, so as to achieve the improvement of the comprehensive performance of the two-phase Mo-Mo5SiB2 alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1a It is a scanned image of large-sized flaky molybdenum powder in the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention;
[0019] Figure 1b It is a scanned image of small-sized flaky molybdenum powder in the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention;
[0020] Figure 2a It is a microstructure scanning diagram of the two-phase Mo-Mo5SiB2 alloy obtained in Example 3 of the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention;
[0021] Figure 2b This is a metallographic photograph of the two-phase Mo-Mo5SiB2 alloy obtained in Example 3 of the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention. DETAILED DESCRIPTION
[0022] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] The preparation method of the two-phase Mo-Mo5SiB2 alloy comprises the following steps:
[0024] Step 1: Pour Mo powders of different sizes and anhydrous ethanol into a beaker at a mass ratio of 1 to 5:1, pour out the upper liquid after ultrasonic treatment, retain the large-sized powder in the lower layer, and repeat the ultrasonic screening several times; then place it in a vacuum drying oven for drying at a temperature of 80°C to 150°C for 12h to 24h, and finally sieve it through 300 mesh to obtain 300-mesh Mo powder. Large-sized Mo powders with uniform size can fully contact with grinding balls and grinding jars during drum ball milling, so that more spherical Mo powders are deformed into flakes. In addition, Mo with continuous distribution and coarse grains can increase the probability of crack capture and crack bridging in the two-phase alloy during deformation and fracture, thereby further improving its fracture toughness.
[0025] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 1:1 to 5:1, perform drum ball milling after packaging, and then dry to obtain flaky molybdenum powder; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball is made of alumina, and the ball milling parameters are: rotation speed 300 to 500 rpm, ball-to-material ratio 3:1 to 10:1, and ball milling time 10h to 20h. The spherical Mo powder is prepared into flakes by drum ball milling to obtain a thin sheet structure with a large specific surface area. In the mixed powder of flaky Mo powder and spherical T2 powder, the probability and degree of mutual contact are high. In the subsequent hot pressing sintering process, it is easy to achieve continuous distribution of Mo phase, which can improve the ability of crack capture and crack bridging during alloy deformation and fracture, thereby improving toughness.
[0026] Step 3: Low-energy ball milling of the flaky molybdenum powder and the T2 phase powder. In a planetary ball mill, the two powders are dispersed by grinding balls and the grinding pot is driven to rotate by mechanical energy, so that the two-phase powder is evenly mixed in the process. The volume fraction of Mo powder is 30%-50%, and the volume fraction of T2 phase powder is 50%-70%. The ball mill and grinding balls used in the ball milling process are made of agate. The ball milling parameters are: rotation speed 300rpm, effective time 6h, ball-to-material ratio 1:1, and Mo-Si-B two-phase mixed powder is obtained;
[0027] Step 4: Since the Mo phase and the T2 phase can maintain their own phase structure during the sintering process, the prefabricated Mo-Si-B two-phase mixed powder is placed in a graphite mold for hot pressing and sintering, and after cooling, a two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution is obtained; the parameters of the hot pressing and sintering process are: temperature of 1500℃~1600℃, heating rate of 10℃ / min, 7×10 -3 Pa~1×10 -2 Pa vacuum environment, the hot pressing pressure is 40-45MPa, and the time is 2h-6h.
[0028] Through the above manner, the preparation method of the two-phase Mo-Mo5SiB2 alloy of the present invention prepares flaky Mo powder with a smooth surface and no cracks under the conditions of adjusting the ball-to-material ratio, rotation speed and ball milling time, and mixes it with T2 phase powder in a certain proportion. Because the flaky Mo powder has a higher specific surface area, in the mixed powder of flaky Mo powder and spherical T2 powder, the probability and degree of mutual contact are higher. In the subsequent hot pressing and sintering process, it is easy to achieve continuous distribution of Mo phase, which can improve the ability of crack capture and crack bridging during alloy deformation and fracture, and use less Mo content to obtain a continuously distributed structure of molybdenum phase, thereby improving the fracture toughness of the alloy; the two-phase Mo-Mo5SiB2 alloy obtained by the present invention has a room temperature fracture toughness of 11.4MPam1 / 2 to 18.49MPam1 / 2, which is significantly higher than the fracture toughness of the two-phase alloy of similar composition in the prior art, and the improvement is 57% to 64%, which can explain that the Mo-Mo5SiB2 alloy prepared by the method of the present invention can achieve continuous distribution of molybdenum phase when its Mo content is 30%-40%.
[0029] Example 1
[0030] Step 1, Mo powders of different sizes and anhydrous ethanol are poured into a beaker at a mass ratio of 5:1, and the upper liquid is poured out after ultrasonic treatment for 10 minutes, and the large-sized powders in the lower layer are retained, and the ultrasonic screening is repeated 3 times; then it is placed in a vacuum drying oven for drying at a temperature of 80°C for 12 hours, and finally sieved with 300 mesh to obtain 300 mesh Mo powder;
[0031] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 1:1, package and perform drum ball milling, and then dry to obtain large-sized flaky molybdenum powder with a large specific surface area, as shown in 1a; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball material is alumina, and the ball milling parameters are: rotation speed 300rpm, ball-to-material ratio 3:1, and ball milling time 10h.
[0032] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 30%, and the volume fraction of the T2 phase powder is 70%. The ball milling jar and the grinding balls used in the ball milling process are made of agate, and the ball milling parameters are: rotation speed 300rpm, effective time 6h, ball-to-material ratio 1:1, to obtain Mo-Si-B two-phase mixed powder;
[0033] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1500°C, heating rate of 10°C / min, 7×10 -3Pa vacuum environment, hot pressing pressure of 40MPa, time of 2h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, and the room temperature fracture toughness of the alloy was measured to be 11.4MPa·m 1 / 2 .
[0034] Example 2
[0035] Step 1, Mo powders of different sizes and anhydrous ethanol are poured into a beaker at a mass ratio of 5:1, and the upper liquid is poured out after ultrasonic treatment for 10 minutes, and the large-sized powders in the lower layer are retained, and the ultrasonic screening is repeated 3 times; then it is placed in a vacuum drying oven for drying at a temperature of 80°C for 12 hours, and finally sieved with 300 mesh to obtain 300 mesh Mo powder;
[0036] Step 2: Mo powder and anhydrous ethanol are placed in a polyethylene tank at a mass ratio of 1:1, packaged, and then subjected to drum ball milling, followed by drying to obtain a large-sized powder with a large specific surface area, such as Figure 1b As shown; the ball mill jar used in the ball milling process is made of polyethylene, the grinding balls are made of alumina, and the ball milling parameters are: rotation speed 300 rpm, ball-to-material ratio 3:1, and ball milling time 10 h.
[0037] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 30%, and the volume fraction of the T2 phase powder is 70%. The ball milling jar and the grinding balls used in the ball milling process are made of agate, and the ball milling parameters are: rotation speed 300rpm, effective time 6h, ball-to-material ratio 1:1, to obtain Mo-Si-B two-phase mixed powder;
[0038] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1600°C, heating rate of 10°C / min, 7×10 -3 Pa vacuum environment, hot pressing pressure of 45MPa, time of 3h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, and the room temperature fracture toughness of the alloy was measured to be 13.5MPa·m 1 / 2 .
[0039] Example 3
[0040] Step 1, pour Mo powders of different sizes and anhydrous ethanol into a beaker at a mass ratio of 5:1, pour out the upper liquid after ultrasonication for 10 minutes, retain the large-sized powders in the lower layer, and repeat ultrasonic screening 3 times; then place it in a vacuum drying oven for drying at 80°C for 24 hours, and finally sieve it through 300 mesh to obtain 300 mesh Mo powder;
[0041] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 1:1, perform drum ball milling after packaging, and then dry to obtain flaky molybdenum powder with a large specific surface area, as shown in Figure 1; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball material is alumina, and the ball milling parameters are: rotation speed 300rpm, ball-to-material ratio 5:1, and ball milling time 10h.
[0042] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 40%, and the volume fraction of the T2 phase powder is 60%. The ball milling jar and the grinding balls used in the ball milling process are made of agate. The ball milling parameters are: rotation speed 300 rpm, effective time 6 h, ball-to-material ratio 1:1, and Mo-Si-B two-phase mixed powder is obtained;
[0043] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1600°C, heating rate of 10°C / min, 7×10 -3 Pa vacuum environment, hot pressing pressure of 40MPa, time of 3h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, such as Figure 2a -b, and the room temperature fracture toughness of the alloy was measured to be 15.4MPa·m 1 / 2 .
[0044] Example 4
[0045] Step 1, Mo powders of different sizes and anhydrous ethanol are poured into a beaker at a mass ratio of 5:1, and the upper liquid is poured out after ultrasonic treatment for 10 minutes, and the large-sized powders in the lower layer are retained, and ultrasonic screening is repeated several times; then it is placed in a vacuum drying oven for drying at a temperature of 80°C for 24 hours, and finally sieved through 300 mesh to obtain 300 mesh Mo powder;
[0046] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 1:1, package and perform drum ball milling, and then dry to obtain flaky molybdenum powder with a large specific surface area, as shown in Figure 1; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball is made of alumina, and the ball milling parameters are: rotation speed 500rpm, ball-to-material ratio 5:1, and ball milling time 10h.
[0047] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 40%, and the volume fraction of the T2 phase powder is 60%. The ball milling jar and the grinding balls used in the ball milling process are made of agate. The ball milling parameters are: rotation speed 300 rpm, effective time 6 h, ball-to-material ratio 1:1, and Mo-Si-B two-phase mixed powder is obtained;
[0048] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1600°C, heating rate of 10°C / min, 7×10 -3 Pa vacuum environment, hot pressing pressure of 40MPa, time of 3h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, and the room temperature fracture toughness of the alloy was measured to be 15.9MPa·m 1 / 2 .
[0049] Example 5
[0050] Step 1, Mo powders of different sizes and anhydrous ethanol are poured into a beaker at a mass ratio of 1:1, and the upper liquid is poured out after ultrasonic treatment for 10 minutes, and the large-sized powders in the lower layer are retained, and ultrasonic screening is repeated multiple times; then it is placed in a vacuum drying oven for drying at a temperature of 80°C for 12 hours, and finally sieved through 300 mesh to obtain 300 mesh Mo powder;
[0051] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 1:1, package and perform drum ball milling, and then dry to obtain flaky molybdenum powder with a large specific surface area, as shown in Figure 1; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball is made of alumina, and the ball milling parameters are: rotation speed 300rpm, ball-to-material ratio 10:1, and ball milling time 10h.
[0052] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 40%, and the volume fraction of the T2 phase powder is 60%. The ball milling jar and the grinding balls used in the ball milling process are made of agate. The ball milling parameters are: rotation speed 300 rpm, effective time 6 h, ball-to-material ratio 1:1, and Mo-Si-B two-phase mixed powder is obtained;
[0053] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1600°C, heating rate of 10°C / min, 7×10 -3 Pa vacuum environment, hot pressing pressure of 40MPa, time of 3h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, and the room temperature fracture toughness of the alloy was measured to be 16.3MPa·m 1 / 2 .
[0054] Example 6
[0055] Step 1, Mo powders of different sizes and anhydrous ethanol are poured into a beaker at a mass ratio of 5:1, and the upper liquid is poured out after ultrasonic treatment for 20 minutes, and the large-sized powders in the lower layer are retained, and ultrasonic screening is repeated multiple times; then it is placed in a vacuum drying oven for drying at a temperature of 150°C for 24 hours, and finally sieved with 300 mesh to obtain 300 mesh Mo powder;
[0056] Step 2: Put Mo powder and anhydrous ethanol into a polyethylene jar at a mass ratio of 5:1, perform drum ball milling after packaging, and then dry to obtain flaky molybdenum powder with a large specific surface area, as shown in Figure 1; the ball mill jar used in the ball milling process is made of polyethylene, the grinding ball material is alumina, and the ball milling parameters are: rotation speed 300rpm, ball-to-material ratio 5:1, and ball milling time 20h.
[0057] Step 3, the flaky molybdenum powder and the T2 phase powder are subjected to low-energy ball milling treatment, wherein the volume fraction of the Mo powder is 50%, and the volume fraction of the T2 phase powder is 50%. The ball milling jar and the grinding balls used in the ball milling process are made of agate, and the ball milling parameters are: rotation speed 300rpm, effective time 6h, ball-to-material ratio 1:1, to obtain Mo-Si-B two-phase mixed powder;
[0058] Step 4: Place the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering. The parameters of the hot pressing and sintering process are: temperature of 1600°C, heating rate of 10°C / min, 7×10 -3 Pa vacuum environment, hot pressing pressure of 45MPa, time of 6h, after cooling, two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distribution was obtained, and the room temperature fracture toughness of the alloy was measured to be 18.49MPa·m 1 / 2 .
Claims
1. A method for preparing a two-phase Mo-Mo5SiB2 alloy, characterized in that: The following steps are involved: Step 1, putting Mo powder and anhydrous ethanol into a polyethylene tank, encapsulating and drum-milling, and then drying to obtain flaky molybdenum powder; The ball milling jar used in the ball milling process in step 1 is made of polyethylene, the grinding balls are made of alumina, and the ball milling parameters are: rotation speed 300-500 rpm, ball-to-material ratio 3:1-10:1, and ball milling time 10h-20h; Before step 1, the Mo powder is screened to obtain Mo powder of uniform size; The screening process is as follows: Mo powder and anhydrous ethanol are poured into a beaker, the mass ratio of anhydrous ethanol to powder is 1-5:1, the upper layer of liquid is poured out after ultrasonic treatment, and the lower layer of large-sized powder is retained; then it is placed in a vacuum drying oven for drying, the drying temperature is 80° C.-150° C., the time is 12h-24h, and finally 300 mesh sieving is performed to obtain Mo powder with uniform size; The mass ratio of Mo powder to anhydrous ethanol in step 1 is 1:1 to 5:1; Step 2, subjecting the flaky molybdenum powder and the T2 phase powder to low-energy mixing treatment to obtain a Mo-Si-B two-phase mixed powder; In step 2, the volume fraction of the flaky molybdenum powder is 30%-50%, and the volume fraction of the T2 phase powder is 50%-70%; Step 3, placing the Mo-Si-B two-phase mixed powder in a graphite mold for hot pressing and sintering, and obtaining a two-phase Mo-Mo5SiB2 alloy with different continuous molybdenum distributions after cooling; The parameters of the hot pressing sintering process in step 3 are: temperature 1500℃~1600℃, heating rate 10℃ / min, 7×10 - 3 Pa~1×10 -2 Pa vacuum environment, the hot pressing pressure is 40~45MPa, and the time is 2h~6h.
2. The method for preparing the two-phase Mo-Mo5SiB2 alloy according to claim 1, characterized in that: The mixing process in step 2 is ball milling. The ball milling jar and grinding balls used in the ball milling process are both made of agate. The ball milling parameters are: rotation speed 300 rpm, effective time 6 hours, and ball-to-material ratio of 1:1.
Citation Information
Patent Citations
Heat-resistant molybdenum alloy
US20140141281A1